A spirometric and cephalometric comparative evaluation of mandibular advancement devices and occlusal jig - Shaily Ujjwal; Pragati Kaurani; U Narendra Padiyar; Sudhir Meena; Devendra Pal Singh; Hemant Kr Sharma (Wolters Kluwer Medknow Publications, 2019)
Aim: Aim of the current study was to evaluate the effect of occlusal jig with increased vertical dimension and mandibular advancement device on the oropharangeal volume in completely edentulous patients using spirometry and cephalometry. Materials and Methods: The current study included includes 30 completely edentulous patient according to inclusion criteria. They were each subjected to cephalometric and spirometric analysis wearing CCD, OJ & MAD. Results obtained were subjected to following statistical analysis, one-way ANOVA test, unpaired t-test, and Dunnett's test. Result: Both OJ & MAD brings about significant change in oropharangeal volume hence both the devices are effective treatment of choice for OSA, while greater increase was observed in oropharangealvolume of OJ as compared to MAD. Spirometric analysis shows insignificant changes in the oropharangeal volume caused by MAD while OJ causes small but significant change in oropharangeal volume (PIFR]. Conclusion: Within the limitation of the study, it can be concluded that, on cephalometric & spirometric evaluation, OJ shows greater increase in oropharangeal volume when compared to MAD in completely edentulous patient.